Novels, 1881-1886 - James, Henry, 1843-1916 (New York, N.Y. : Literary Classics of the United States, 1985)
Washington Square -- The portrait of a lady -- The Bostonians.
Washington Square -- The portrait of a lady -- The Bostonians.
Keywords: American literature; American fiction -- 19th century; American literature -- 19th century